Knowledge of Nurses towards Post-exposure Prophylaxis for HIV infection at a Tertiary Health Care Center - Shrestha, Sirjana (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Acquired immunodeficiency syndrome is a chronic, potentially life-threatening condition caused by the human immunodeficiency virus in which progressive failure of immune system allows life threatening opportunistic infection and cancer to thrive. Post exposure prophylaxis is preventive medical treatment recommended immediately after exposure to a pathogen. The objective of this research is to assess the level of knowledge regarding PEP of HIV among nurses. Methods An analytical cross sectional study was conducted among 164 nurses to assess the knowledge regarding PEP of HIV among nurses at the College of Medical Sciences and Teaching Hospital, Bharatpur. Data was collected using probability random sampling using self-structured questionnaire. Data was entered and analyzed using in statistical package for social science (SPSS) version 23 using descriptive and inferential statistical tools. Results Among the 164 nurses, more than half (56.1%) were in the age 20-25years and had completed their PCL Nursing. Likewise, 35.4% had 2-4 years of experience. Also, 55.5% had a moderate level of knowledge, 18.9% had an inadequate level and 25.6% had adequate knowledge of PEP of HIV. The result of mean ± SD of knowledge was 11.18±3.125. There is statistically significant association between levels of knowledge with working area and total working experience. Conclusions The study shows that only 25.6% had adequate knowledge regarding PEP of HIV. Therefore, nurses should be up to date with their knowledge; engage in workshop and training programs periodically.